Exploring the development of a strategy and tactics to sweeten suppliers : a case study of a European sugar producer - Riecken, Johanna (SLU/Dept. of Economics, 2018)
Buyer-supplier relationships can be important sources of value for both sides. From the buyer’s perspective, suppliers can ensure the access to critical resources that the buyer needs for the production of its goods. With the EU market deregulation, the competition on the European sugar market increased, where sugar is produced from sugar beets. Sugar beet prices dropped and reduced the profitability of sugar beet growing. Sugar producers subsequently face an increased competition, also for accessing the critical resource sugar beets, which is determining for the company’s survival. To ensure the access to sugar beets, sugar producers need to develop improved buyer-supplier relationships, that also hold under the new market circumstances.